Effect of the collector geometry in the concentrating photovoltaic thermal solar cell performance - Torres Joao Paulo N. (Thermal Science, 2018)
The aim of this work is the redesign of the reflector geometry in hybrid concentrating collectors that are currently manufactured by SOLARUS Sunpower AB** to improve the energy efficiency of their solar collectors. The analysis is first accomplished using a numerical model that uses geometrical optics to study the interaction between the sunlight and a concentrating collector along the year. More complex physical models based on open-source and advanced object-oriented Monte Carlo ray tracing programs (SolTrace, Tonatiuh) have been used to study the relation between the collector annual performance and its geometry. On an annual performance basis, a comparative analysis between several solar collector geometries was effectuated to search for higher efficiencies but with controlled costs. Results show that efficiency is deeply influenced by reflector geometry details, collector tilt and location (latitude, longitude) of the solar panel installation and, mostly, by costumer demands. Undoubtedly, the methodology presented in this paper for the design of the solar collector represents an important tool to optimize the binomial cost/effectiveness photovoltaic performance in the energy conversion process. The results also indicate that some modified concentrating solar collectors are promising when evaluating the yearly averaged energy produced per unit area, leading to evident improvements in the performance when compared to the current standard solar concentrating SOLARUS systems. Increases of about 50% (from 0.123 kW/m2 to 0.1832 kW/m2) were obtained for the yearly average collected power per reflector area when decreasing the collector height in 3.5% (from 143 mm to 138 mm).